Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am wanting to find the height in the barometric equations below. Could anyone solve this?

Equation 1: $$ {P}=P_b \cdot \left[\frac{T_b}{T_b + L_b\cdot(h-h_b)}\right]^{\textstyle \frac{g_0 \cdot M}{R^* \cdot L_b}} $$

Equation 2: $$ P=P_b \cdot \exp \left[\frac{-g_0 \cdot M \cdot (h-h_b)}{R^* \cdot T_b}\right] $$

where

  • $P_b =$ Static pressure (pascals)
  • $T_b =$ Standard temperature ([[kelvin|K]])
  • $L_b =$ Standard temperature lapse rate -0.0065 (K/m) in [[International Standard Atmosphere|ISA]]
  • $h =$ Height above sea level (meters)
  • $h_b =$ Height at bottom of layer b (meters; e.g., h_1 = 11,000 meters)
  • $R^* =$ [[Universal gas constant]] for air: 8.31432 N·m /(mol·K)
  • $g_0 =$ Gravitational acceleration (9.80665 m/s2)
  • $M =$ Molar mass of Earth's air (0.0289644 kg/mol)
share|improve this question
    
Do you know about logarithms? Take logs of both sides. –  Ben Crowell Feb 12 '12 at 5:11
    
@Ben : As Gerry mentioned, logarithms were not necessary here. The first equation was enough. –  Patrick Da Silva Feb 12 '12 at 5:23
    
Caleb, the two equations aren't equivalent. Do you understand under which circumstances one might be valid and the other invalid? @Patrick Da Silva: You're right, of course, that logs aren't needed for 1; however, that doesn't help caleb unless he has a good reason to believe that 1 works for his situation -- in which case why does he have 2? 2 assumes constant temperature, whereas 1 appears to be taking into account the decrease of temperature with altitude. 1 looks to me like it is going to be a better approximation over a small range of altitudes, but not at extremely high altitudes. –  Ben Crowell Feb 12 '12 at 6:14
    
@BenCrowell: Yes, I know I need the 2 equations. One for lower altitudes, and the other for higher. –  caleb Feb 12 '12 at 7:07
    
@caleb: Are you going to interpolate between them? –  Ben Crowell Feb 12 '12 at 16:07

2 Answers 2

up vote 1 down vote accepted

Equation $1$ :

$$\left[\frac{T_b}{T_b + L_b\cdot(h-h_b)}\right]^{\textstyle \frac{g_0 \cdot M}{R^* \cdot L_b}} = \frac {P}{P_b} \Rightarrow \left[\frac{T_b}{T_b + L_b\cdot(h-h_b)}\right] =\left(\frac {P}{P_b}\right)^{\textstyle \frac{R^* \cdot L_b}{g_0 \cdot M}} \Rightarrow$$

$$\Rightarrow T_b+L_b(h-h_b)=T_b\cdot \left(\frac {P_b}{P}\right)^{\textstyle \frac{R^* \cdot L_b}{g_0 \cdot M}} \Rightarrow L_b(h-h_b)=T_b\left(\left(\frac {P_b}{P}\right)^{\textstyle \frac{R^* \cdot L_b}{g_0 \cdot M}}-1\right)\Rightarrow$$

$$\Rightarrow h = h_b+ \frac{T_b}{L_b}\left(\left(\frac {P_b}{P}\right)^{\textstyle \frac{R^* \cdot L_b}{g_0 \cdot M}}-1\right)$$

Equation $2$ :

$$\left[\frac{-g_0 \cdot M \cdot (h-h_b)}{R^* \cdot T_b}\right] = \ln \left(\frac {P}{P_b}\right) \Rightarrow -g_0 \cdot M \cdot(h-h_b)=R^* \cdot T_b \cdot \ln \left(\frac {P}{P_b}\right) \Rightarrow$$

$$\Rightarrow h = h_b - \frac {R^* \cdot T_b}{g_0 \cdot M} \cdot \ln \left(\frac {P}{P_b}\right)$$

share|improve this answer

In the 1st one: start with $P$, divide by $P_b$, raise to the power $R^*L_b/g_oM$, take the reciprocal, multiply by $T_b$, subtract $T_b$, divide by $L_b$, and add $h_b$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.